Skin Toxicity After Exposure to Gadolinium-Based Contrast Agents in Normal Renal Function, Using Clinical Approved Doses: Current Status of Preclinical and Clinical Studies - Parillo, Marco; Mallio, Carlo A; Van der Molen, Aart J; Rovira, Àlex; Ramalho, Joana; Ramalho, Miguel; Gianolio, Eliana; Karst, Uwe; Radbruch, Alexander; Stroomberg, Gerard; Clement, Olivier; Dekkers, Ilona A; et al. (Investigative radiology, 2023)
The aim of this study was to summarize the current preclinical and clinical evidence on the association between exposure to gadolinium (Gd) compounds and skin toxicity in a setting similar to clinical practice. A search of MEDLINE and PubMed references from January 2000 to December 2022 was performed using keywords related to gadolinium deposition and its effects on the skin, such as "gadolinium," "gadolinium-based contrast agents," "skin," "deposition," and "toxicity." In addition, cross-referencing was added when appropriate. For preclinical in vitro studies, we included all the studies that analyzed the response of human dermal fibroblasts to exposure to various gadolinium compounds. For preclinical animal studies and clinical studies, we included only those that analyzed animals or patients with preserved renal function (estimated glomerular filtration rate >30 mL/min/1.73 m 2 ), using a dosage of gadolinium-based contrast agents (GBCAs) similar to that commonly applied (0.1 mmol/kg). Forty studies were selected. Preclinical findings suggest that Gd compounds can produce profibrotic responses in the skin in vitro, through the activation and proliferation of dermal fibroblasts and promoting their myofibroblast differentiation. Gadolinium influences the process of collagen production and the collagen content of skin, by increasing the levels of matrix metalloproteinase-1 and tissue inhibitor of metalloproteinase-1. Preclinical animal studies show that Gd can deposit in the skin with higher concentrations when linear GBCAs are applied. However, these deposits decrease over time and are not associated with obvious macroscopic or histological modifications. The clinical relevance of GBCAs in inducing small fiber neuropathy remains to be determined. Clinical studies show that Gd is detectable in the skin and hair of subjects with normal renal function in higher concentrations after intravenous administration of linear compared with macrocyclic GBCA. However, these deposits decrease over time and are not associated with cutaneous or histological modifications. Also, subclinical dermal involvement related to linear GBCA exposure may be detectable on brain MRI. There is no conclusive evidence to support a causal relationship between GBCA administration at the clinical dose and cutaneous manifestations in patients with normal renal function. Gadolinium can produce profibrotic responses in the skin, especially acting on fibroblasts, as shown by preclinical in vitro studies. Gadolinium deposits are detectable in the skin even in subjects with normal renal function with higher concentrations when linear GBCAs are used, as confirmed by both preclinical animal and human studies. There is no proof to date of a cause-effect relationship between GBCA administration at clinical doses and cutaneous consequences in patients with normal renal function. Multiple factors, yet to be determined, should be considered for sporadic patients with normal renal function who develop clinical skin manifestations temporally related to GBCA administration.